Self-bound droplet formation in two coupled Bose-Einstein condensates - Chiquillo Márquez, Emerson Evaristo [UNESP] (2025)
The main subject of this work is research the stable formation of droplets in Bose-Bose gases considering some extra elements to those already known in the description of conventional droplets. To this end, the study is carried out mainly through an effective quantum field theory in the the path-integral formalism. To ensure that the physical results are finite, we also use some basic aspects of renormalization by counterterms including regularization methods. So, we set key findings regarding to droplets with nonuniversal corrections to the interactions, in three, two, and one dimension, both at zero and finite temperature. We include three-dimensional Rabi-coupled droplets with nonuniversal corrections to the interactions at zero temperature. Droplets in two coupled Bose-Einstein condensates with dipole-dipole interactions both at zero and finite temperature are also explored.